Design and manufacture (He-Ne) laser windows multiplayer antireflection coating - Ghazai , Alaa (University of Thi-Qar Journal of Science, 2019)
In this study;the windows of (He-Ne) laser multilayer antireflection coating have been designed from materials MgF as external layer with refractive index (1.38) and ZnS as internal layer with refractive index (2.35) deposited on BK-7 glass that have refractive index (1.52). Five layers with 2 optical path equal quarter wavelength (/4) theoretically and experimentally, and another way, five layers with middle layer (/2) theoretically were used. The all designs are dealing with them in the wavelength less than design of wavelength with clear difference of the theoretical design with middle layer (/2) at design wavelength. The value of minimum reflectance to one about (0.002) at (680) nm theoretically and (0.0081) at (590)nm while experimentally about (0.69) at (650)nm. Another way we obtains on refraction about (0.0040) in a wide range from wavelength (450 - 690)nm when the seven layer with optical path equal quarter wavelength (/4) theoretically were designed .